Ternary mixture of Portland cement, blast furnace slag and limestone: Mechanical Strength and Durability - E. Díaz, Jherson; R. Izquierdo, Silvia; Mejía de Gutiérrez, Ruby; Gordillo S., Marisol (Revista de la Construcción. Journal of Construction, 2013)
The blended cements based on partial replacement of cement by other minerals and / or industrial by-products arise as a technically and environmentally sustainable alternative. These cements are based on the introduction of two or more additions for better final properties through the synergistic effects of its components. The present research examines the effect on the performance properties of Portland cement with addition of limestone (up to 20%) and blast furnace slag (up to 30%), to generate a ternary mixture. The compressive strength, absorption and porosity, capillary suction, chloride permeability, and chemical resistance of mortars exposed to sulfates were evaluated. The results show that the compressive strength of the cements ternary is up to 35% higher with respect to the reference mortar and in turn have lower coefficients of capillary suction, confirming the action of both physical and chemical nature of the materials addition. The best performance of resistance to sulfates attack was found in mixture with minor proportion of limestone. The characterization of the reaction products was performed using X-ray diffraction and scanning electron microscopy.